Folding for the Immune Synapse: CCT Chaperonin and the Cytoskeleton - Martín-Cófreces, Noa Beatriz; Valpuesta, José María; Sánchez-Madrid, Francisco (Frontiers in Cell and Developmental Biology, 2021)
Lymphocytes rearrange their shape, membrane receptors and organelles during cognate contacts with antigen-presenting cells (APCs). Activation of T cells by APCs through pMHC-TCR/CD3 interaction (peptide-major histocompatibility complex-T cell receptor/CD3 complexes) involves different steps that lead to the reorganization of the cytoskeleton and organelles and, eventually, nuclear activation. Both the positioning of the lymphocyte centrosome in close proximity to the APC and the nucleation of a dense microtubule network beneath the plasma membrane from the centrosome support the T cell’s intracellular polarity. Signaling from the TCR is facilitated by this traffic, which constitutes an important pathway for regulation of T cell activation. The coordinated enrichment upon T cell stimulation of the chaperonin CCT (chaperonin-containing tailless complex polypeptide 1; also termed TRiC) and tubulins at the centrosome area support polarized tubulin polymerization and T cell activation. The functional role of this chaperonin in regulating cytoskeletal composition and dynamics at the immune synapse are discussed.